2007
DOI: 10.1111/j.1582-4934.2007.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking translocation of cell surface molecules from the ER to the cell surface by intracellular antibodies targeted to the ER

Abstract: Intracellular antibodies (intrabodies) constitute a potent tool to neutralize the function of target proteins inside specific cell compartments (cytosol, nucleus, mitochondria and ER). The intrabody technology is an attractive alternative to the generation of gene-targeted knockout animals and complements or replaces knockdown techniques such as antisense-RNA, RNAi and RNA aptamers. This article focuses on intrabodies targeted to the ER. Intracellular anti-bodies expressed and retained inside the ER (ER intrab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 109 publications
(238 reference statements)
0
34
0
Order By: Relevance
“…These data indicate that mutant TIMP-3 has distinctive effects on the early steps of maturation of the receptor. It has been recently reported that novel highly efficient intrabodies can bind newly synthesized VEGFR-2 in the endoplasmic reticulum and block receptor transport to the cell surface (37,38). It is an interesting possibility that WT and mutant TIMP-3 may differentially affect immature receptor translocation via distinct interactions with newly synthesized VEGFR-2 in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that mutant TIMP-3 has distinctive effects on the early steps of maturation of the receptor. It has been recently reported that novel highly efficient intrabodies can bind newly synthesized VEGFR-2 in the endoplasmic reticulum and block receptor transport to the cell surface (37,38). It is an interesting possibility that WT and mutant TIMP-3 may differentially affect immature receptor translocation via distinct interactions with newly synthesized VEGFR-2 in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…The method has been successfully applied to many targets, including human IL2 receptor, ErbB-2 receptor, b-amyloid precursor protein and VCAM1. 6,[17][18][19][20][21] Other subcellular compartments could be targeted by adding suitable signal sequences. 19,22 Functional studies of membrane receptors or secreted proteins ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Intrabodiesmentioning
confidence: 99%
“…In addition, their biochemical properties can be changed at will, e.g., by fusion to other protein domains, or they can even be immediately expressed inside the living cell to induce knockdown phenotypes. 6,7 The usefulness of antibodies in visualization or the knockdown of protein functions in the living cell has been proven by microinjection, [8][9][10][11][12] which demonstrated the stability and function of mature antibodies in the living cytoplasm. However, examples published since the first report of this method are scarce, mainly *Correspondence to: Stefan Dübel; Email: s.duebel@tu-bs.de Submitted: 10/13/10; Accepted: 11/04/10 DOI: 10.4161/mabs.3.…”
Section: Introductionmentioning
confidence: 99%
“…To bypass any lack of specificity, we used an intrabody with intrinsic specificity for its target [18,19]. Intrabodies can be targeted to the nucleus, mitochondria or endoplasmic reticulum (ER), where they bind their target proteins and thus persistently inhibit their function.…”
Section: Introductionmentioning
confidence: 99%
“…Intrabodies can be targeted to the nucleus, mitochondria or endoplasmic reticulum (ER), where they bind their target proteins and thus persistently inhibit their function. For instance, intrabodies targeted to the ER arrest transitory target proteins preventing their further subcellular trafficking [18,19]. Intrabodies are a promising alternative to RNA-based knockdown strategies in cases of failure of the latter [20][21][22].…”
Section: Introductionmentioning
confidence: 99%